(untitled) (Conference on English Language Teaching, 2025)
The study investigated code-mixing and code-switching phenomena in the Indonesian movie The Architecture of Love, finding and analyzing the types, functions, and social dynamics. A descriptive qualitative method was employed in this study, with documentation as a data collection technique. The dialogues were manually transcribed from the film, containing code-mixing and code-switching, using the subtitles as a reference. The result analysis showed 60 data points of code-mixing, insertion was the most dominant type of code-mixing (75.44%), while of the 53 data points of code-switching, inter-sentential switching was the most frequent type (53.85%). These results indicated that speakers prefer inserting English elements within Indonesian structures and shifting between sentences across languages. Furthermore, the analysis identified social functions of 113 data points of code-mixing and code-switching, finding that the expressive function occupied the highest position (41.6%). The expressive function appeared most frequently, showing that emotional expression and personal attitudes play a significant role in character interaction. Regarding social dynamics, the study highlighted solidarity as the dominant relational aspect, followed by power and social distance. This study contributed to understanding how language mixing practices in Indonesian film represent social interaction in multilingual contexts. Also, the study emphasizes that code-mixing and code-switching in this film not only serve linguistic purposes but also reflect complex social relations between characters.